Métricas intrínsecas invariantes à esquerda em grupos de Lie - Azuaite Aramis Schneider (2019)
In this work we deal with Lie groups with left-invariant intrinsic metrics. We define left-invariant Finsler metrics and Carnot-Carathéodory metrics in completely nonholonomic distributions, and we call the Finsler version of the latter metrics by Carnot-Carathéodory-Finsler metrics. The main objective of this work is to prove that all left-invariant intrinsic metric in a Lie group is a Carnot-Carathéodory-Finsler metric. We also study conditions under which the left-invariant intrinsic metrics are Finsler, showing that the metrics that satisfy this condition are characterized by rectifiability of one-parameter subgroups of the Lie group